Castiglione della Pescaia (Grosseto), Italien. »Prile-Projekt« (1. Jt. v. Chr., bes. 6.–1. Jh. v. Chr.). Die Arbeiten der Jahre 2019 bis 2022 - Colombi, Camilla; Hoelzmann, Philipp; Del Segato, Valerj; Langwald, Corinna (e-Forschungsberichte des DAI, 2023)
The »Prile Project« has been investigating since 2016 the relationship between the Etruscan settlement of Vetulonia and the ancient lagoon called Prile. As part of the project, archaeologists and geoscientists are helping to outline and understand the changes in the landscape caused by the past siltation of the lagoon and the subsequent changes in the use of the shores. From 2019 to 2022, three excavation campaigns and one drilling campaign could be carried out, which have brought significant new insights into the extent and development of the lagoon. A monumental Etruscan infrastructure complex not far from the shores of the lagoon was identified and its potential for future research was demonstrated.